KAJIAN HUTAN KOTA MALABAR TERHADAP KENYAMANAN TERMAL - Bado Towary, Eduardo Hilario; Sulistyono, Roedy; Tito, Sama? Iradat; Ferdian, Muh. Agus (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Comfort is something that humans need without exception when in a Green Open Space (RTH). Thermal comfort is a thermal condition felt by humans that is influenced by the environment. The existence of green space such as the City Forest of Malabar needs to be measured about it which can define its feasibility. (1) To examine the effect of thermal comfort in the Malabar forest on the community. (2) Analyzing vegetation in the Malabar city forest related to comfort. The results obtained in this study are the Temperature humidity index (THI) of respondents in the Malabar city forest known to average values of 22.42. It can be categorized that the Malabar city forest has a comfortable condition because in the index range 21 to 24. The analysis of the vegetation analysis in the Malabar city forest is concluded for the predominant vegetation sapling level, ie the pole glodokan plant with an important value index of 6.69. Whereas the pole level that dominates is mahogany with an important value index of 6.66. As for the tree level, the dominant vegetation types are plants with an important value index of 127.91